2014
DOI: 10.1021/op5002676
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Aerobic Alcohol Oxidation Reactions Using a Heterogeneous Ru(OH)x/Al2O3 Catalyst

Abstract: Ru(OH)x/Al2O3 is among the more versatile catalysts for aerobic alcohol oxidation and dehydrogenation of nitrogen heterocycles. Here, we describe the translation of batch reactions to a continuous-flow method that enables high steady-state conversion and single-pass yields in the oxidation of benzylic alcohols and dehydrogenation of indoline. A dilute source of O2 (8% in N2) was used to ensure that the reaction mixture, which employs toluene as the solvent, is nonflammable throughout the process. A packed bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…135 Stahl et al reported a continuous-flow setup for the aerobic oxidation of diverse benzylic and heterobenzylic alcohols. 152 The mesoscale reactor was constructed out of stainless steel tubing (6 mm OD, 76 mm length) and was packed with commercially available Ru(OH)x/Al2O3 (2.3 wt% Ru) catalyst. A diluted source of oxygen (8% in N2) was used as oxidant to stay below the flammability threshold of the solvent.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
See 1 more Smart Citation
“…135 Stahl et al reported a continuous-flow setup for the aerobic oxidation of diverse benzylic and heterobenzylic alcohols. 152 The mesoscale reactor was constructed out of stainless steel tubing (6 mm OD, 76 mm length) and was packed with commercially available Ru(OH)x/Al2O3 (2.3 wt% Ru) catalyst. A diluted source of oxygen (8% in N2) was used as oxidant to stay below the flammability threshold of the solvent.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…Continuous flow aerobic alcohol oxidation using Ru(OH)x/Al2O3 as catalyst and O2 (8% in N2) as source of oxidant. 152 One major advantage of microreactors (compared to batch) is the increased heat-transfer characteristics. 19,154,155 This is attributed to the high surface-to-volume ratios of microchannels.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…On one hand, local shortage of oxygen, caused by the low solubility of oxygen in solvents and poor mass transfer, could potentially limit the reaction rate [11][12][13][14][15][16][17][18][19]. On the other hand, an excess of oxygen might cause overoxidation of products or catalysts [11,[20][21][22]. Mixtures of oxygen and organic solvents under elevated temperatures and pressures could also raise serious safety issues [23].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid residence time  (defined as bed volume/flow rate) was studied with gas flow through determining the system response to the introduction of cinnamaldehyde. The resulting residence time distribution for the normalised response F(t) 35 given by Equation 1, showed a step change, and hence near plug-flow behaviour with relatively little broadening from mixing or axial dispersion (Figure 1). This demonstrates that the catalyst bed was static and filled with well-distributed liquid.…”
mentioning
confidence: 99%